(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The ability of the running firm to pay its debts is thought as liquidity. Therefore, it is crucial to continuously monitor the company’s liquidity condition, without which the organisation cannot continue. Business owners and Managers are concerned with coming up with a plan that would support both maintaining liquidity and boosting profitability. Profitability and liquidity are tightly correlated because one rises while the other falls. Profitability and liquidity are two key factors that might affect a company’s overall performance and capacity to survive. Profitability demonstrates an organization’s capacity to make money from investments, whereas, liquidity measures its capacity to settle short-term liabilities. A study is conducted on a sample of FMCG companies to see whether liquidity effects profitability. The top five FMCG businesses were chosen for the survey, which is based on data collected over a five-years period. The study’s findings indicate that neither the fast ratio nor the current ratio have an impact on return on equity, return on capital employed, or return on assets. The effect of analysis was carried out using SPSS which implies that the profitability of FMCG Companies is unaffected by liquidity.